Dark Chocolate, Dismenore, Santr PENGARUH DARK CHOCOLATE TERHADAP DISMENORE PRIMER PADA SANTRI PUTRI PONDOK PESANTREN AN NUR NGRUKEM BANTUL YOGYAKARTA: desminore - Fatkurrohman, Rizki; Kusumasari, Viantika; Adkhana, Dian (Ruang Ide Publisher, 2024)
Abstract Background: Dysmenorrhea or pain during menstruation is the most common cause of repeated absences from school. This is due to a decrease in learning activity and difficulty concentrating in receiving lessons. Therefore, one of the treatment efforts that can be done to reduce the level of menstrual pain is with Dark Chocolate. Objective: Knowing the effect of dark chocolate on primary dysmenorrhea in female students at the An Nur Ngrukem Islamic boarding school, Bantul, Yogyakarta. Methods: The research design used was pre-experimental using a static-group comparison design approach that had a comparison (control) group. The population of this study were all tahfidz grade 3 female students, totaling 60 students. Consecutive Sampling technique. The research instrument used the Numeric Rating Scale (NRS). The data analysis method uses the Wilcoxon Test & the Mann-Withney Test. Results: Based on the Wilcoxon test, it showed that there was a significant decrease in the pretest and post test for both groups, with a P-Value of 0.000 in the intervention group and a value of 0.014 in the control group, in the mean difference test in the two groups using the Mann-Withney Test with the P-Value is 0.023. Based on these results, the P-Value <0.05 indicates that there is an effect of Dark Chocolate on primary dysmenorrhea in female students at the Islamic boarding school An Nur Bantul, Yogyakarta. Conclusion: Dark chocolate as a nursing intervention that can reduce the intensity of primary dysmenorrhea pain in Islamic boarding school students An Nur Ngrukem Bantul Yogyakarta. Based on the results of the research conducted, respondents were able to use dark chocolate, mixed chocolate/dark compound chocolate, at a dose of 100 grams to reduce the feeling of menstrual pain.